Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.245
|View full text |Cite
|
Sign up to set email alerts
|

Learning Links: A study of narrative learning through games with The Legend of Zelda: Windwaker

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Some teams proposed this game to be autonomously used for incidental vocabulary learning (signs, holes, fireballs, dungeons, leaf pile, stairs, etc.) alongside other educational values such as risk taking and memorization, although previous research works indicated that teacher intervention in the classroom might be necessary to strengthen the pedagogical value of this game [79].…”
Section: Resultsmentioning
confidence: 99%
“…Some teams proposed this game to be autonomously used for incidental vocabulary learning (signs, holes, fireballs, dungeons, leaf pile, stairs, etc.) alongside other educational values such as risk taking and memorization, although previous research works indicated that teacher intervention in the classroom might be necessary to strengthen the pedagogical value of this game [79].…”
Section: Resultsmentioning
confidence: 99%
“…In our review of other studies investigating the use of digital games as part of a language arts or geography curriculum, we observed few examples of researchers providing a detailed summary of how a game was integrated into the day-to-day workings of an elementary or middle school classroom. As with our publication efforts across this and other projects (see for example [2,3,9]) we describe in detail our study design and method for collecting data. It is hoped that this information will be of use for researchers investigating similar questions to our own and/or aid in replication efforts in new contexts and study environments.…”
Section: Observations From the Fieldmentioning
confidence: 99%
“…The third club was girls only and had nine of the previous participants return, tasked with acting as peer mentors to assist nine new participants to learn how to play this game. A detailed discussion the study design and the results of this pilot study are detailed in a previous publication [9].…”
Section: Study 1: Adding Walkthroughs To a Lunchtime Gaming Clubmentioning
confidence: 99%